3D Printing Scaffold Vaccine for Antitumor Immunity (Adv. Mater. 48/2021). Issue 48 (1st December 2021) - Zhang, Yue; Xu, Jialu; Fei, Ziying; Dai, Huaxing; Fan, Qin; Yang, Qianyu; Chen, Yitong; Wang, Beilei; Wang, Chao
Abstract : Cancer Immunotherapy In article number 2106768, Chao Wang and co‐workers develop a 3D‐printed scaffold loaded with immunoregulators for enhanced cancer immunotherapy. The 3D‐scaffold with porous structure endows the system with similar functions to real lymphoid organs by the recruitment of a large number of immune cells, leading to the formation of "artificial tertiary lymphoid structures" (aTLS), which are promising sites to enhance both humoral and cellular immune responses. Efficient anticancer immunity is induced when combined with immune checkpoint blockade (ICB) to inhibit tumor growth and metastasis.